Cosmic ray acceleration to ultrahigh energy in radio galaxies - Matthews, J; Bell, A; Araudo, A; Blundell, K (EDP Sciences, 2019)
The origin of ultrahigh energy cosmic rays (UHECRs) is an open question. In this proceeding, we first review the general physical requirements that a source must meet for acceleration to 10-100 EeV, including the consideration that the shock is not highly relativistic. We show that shocks in the backflows of radio galaxies can meet these requirements. We discuss a model in which giant-lobed radio galaxies such as Centaurus A and Fornax A act as slowly-leaking UHECR reservoirs, with the UHECRs being accelerated during a more powerful past episode. We also show that Centaurus A, Fornax A and other radio galaxies may explain the observed anisotropies in data from the Pierre Auger Observatory, before examining some of the difficulties in associating UHECR anisotropies with astrophysical sources.